2020
DOI: 10.1186/s12889-020-09347-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of village health workers on hospital admission rates and their economic impact in the Kingdom of Bhutan

Abstract: Background Village health workers (VHWs) in Bhutan play an all-encompassing role in supporting the health of their communities. Recent reports from the Bhutan Ministry of Health have indicated a sharp reduction in the number of working VHWs. As such, our work attempts to estimate the cost saved and the number of averted hospital admissions onto the Bhutanese healthcare system and the individuals who are served by these health workers. Methods We utilized a dataset from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Likewise, immunization coverage was as high as 95% in 2010. Such substantial health achievements are, at least, partly attributable to the 'one village health worker per each health center' initiative put in place at the grassroots level by the Royal Government of Bhutan [86]. Moreover, all the health services are state funded and provided for free, as guaranteed in the constitution of Bhutan.…”
Section: Healthmentioning
confidence: 99%
“…Likewise, immunization coverage was as high as 95% in 2010. Such substantial health achievements are, at least, partly attributable to the 'one village health worker per each health center' initiative put in place at the grassroots level by the Royal Government of Bhutan [86]. Moreover, all the health services are state funded and provided for free, as guaranteed in the constitution of Bhutan.…”
Section: Healthmentioning
confidence: 99%
“…Using prior research from our team, we reveal that there is a clear economic argument for investing in the VHWs program as well as expanding training and programing based on the urban-rural divide. 5 The role of CHWs in developing nations can be as straightforward as dispensing basic medications or as involved as providing mental health counseling for vulnerable communities. 6 It is essential to note, that the level of participation of CHWs within their communities is entirely based on the institutions and governments which back them.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in previous research, data from over 95% of all reported disease admissions within Bhutan were used to model the cost-savings associated with VHWs. 5 . These findings demonstrated that for every VHW that was added to Bhutan not only were their costs saved for the healthcare system, but also hospital admissions were averted, and money was saved in the form of lost wages and transportation.…”
Section: Introductionmentioning
confidence: 99%